(untitled) (Praxis Educativa, 2018)
From the Complex Thought perspective, this research aims to analyze the students’ life experience during the early college years. Three fundamental principles proposed by Edgar Morin (dialogic, holographic and organizational recursion) were a theoretical framework. From the qualitative methodology, the in-depth interview technique was applied to students with different educational paths. The findings were organized around three categories: autonomy/dependency, study/ work and continuity /discontinuity.